Fully Condensed Poly (Triazine Imide) Crystals: Extended π‐Conjugation and Structural Defects for Overall Water Splitting. Issue 2 (2nd December 2021) - Liu, Minghui; Wei, Changgeng; Zhuzhang, Hangyu; Zhou, Jingmin; Pan, Zhiming; Lin, Wei; Yu, Zhiyang; Zhang, Guigang; Wang, Xinchen
Abstract: Conventional polymerization for the synthesis of carbon nitride usually generates amorphous heptazine‐based melon with an abundance of undesired structural defects, which function as charge carrier recombination centers to decrease the photocatalytic efficiency. Herein, a fully condensed poly (triazine imide) crystal with extended π‐conjugation and deficient structure defects was obtained by conducting the polycondensation in a mild molten salt of LiCl/NaCl. The melting point of the binary LiCl/NaCl system is around 550 °C, which substantially restrain the depolymerization of triazine units and extend the π‐conjugation. The optimized polymeric carbon nitride crystal exhibits a high apparent quantum efficiency of 12 % ( λ =365 nm) for hydrogen production by one‐step excitation overall water splitting, owing to the efficient exciton dissociation and the subsequent fast transfer of charge carriers. Abstract : A fully condensed poly (triazine imide) crystal, which features extended π‐conjugation and deficient structural defects, decorated with Pt and CoOx as redox cocatalysts efficiently drives the one‐step excitation overall water splitting for H2 and O2 production with a record apparent quantum efficiency of 12 % at 365 nm.